Beyond Capacity-Based Imago Dei: A Relational–Teleological Model for Theological Anthropology in the Age of Generative AI - Hestyn Natal Istinatun; Louisa Marga Metekohy (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2026)
This study examines theological claims concerning Imago Dei—particularly substantive, functional, and relational models—as its unit of analysis, in light of the rise of generative artificial intelligence capable of mimicking cognitive, linguistic, and social performance. The study aims to critically reassess the adequacy of these models and to formulate a more resilient theological framework that preserves human dignity without reducing it to measurable capacities or simulated interactions. Methodologically, the article employs a systematic-critical conceptual review of theological anthropology and interdisciplinary AI literature, combined with comparative analysis and systematic theological synthesis. The findings indicate that capacity-based interpretations render substantive and functional models vulnerable to technological replication, while purely relational accounts risk collapsing into phenomenological simulation. As a conceptual novelty, the article proposes a relational–teleological model of Imago Dei grounded in covenantal participation, vocational orientation, and embodied social existence. This model distinguishes between performative similarity and ontological participation, thereby clarifying the theological boundaries between human persons and AI systems. The study contributes to systematic theology by offering a coherent doctrinal reconstruction that is both conceptually robust and contextually responsive, while also providing a normative framework for evaluating AI in ethical, ecclesial, and public contexts.